CONDITIONS FOR ORGANIZING INDEPENDENT EDUCATION OF STUDENTS BASED ON ARTIFICIAL INTELLIGENCE - Xolmurodov , Behzod (Scientific practical conference, 2025)
The rapid development of information and communication technologies is creating fundamental reforms, innovative approaches and new opportunities in all spheres of society. The education system is not left behind by these changes, it is being updated and improved on the basis of advanced technologies. In recent years, the widespread application of artificial intelligence (AI) technologies in the educational process has become important in automating educational activities, developing personalized teaching methods, increasing efficiency and supporting the pedagogical process.